Gestión administrativa y compromiso docente de una universidad particular del distrito de Santiago de Surco 2019 - Estela Estela, Adán Humberto (2022)
Abstract The objective was to determine how Administrative Management affects the commitment of the university professor of a particular university in the Surco District 2019. Type of quantitative, descriptive - correlational, nonexperimental cross-sectional research. Population, teachers of the first academic semester of 2019, a sample of 150 teachers. Questionnaire with 32 questions adapted to the reality of the teacher, pertinent to the variables and dimensions with the Likert scale. The results showed that the Administrative Management and the Teaching Commitment was very adequate according to 65%, 27% indicated that it is adequate and 8% said as inadequate; The results show the trend of administrative management to the level of very adequate according to 65% of respondents. Specifically, by increasing administrative management increases the commitment of the professor in the private university, contribute to compliance in a timely manner, reaching the commitment of the teacher who will support the exercise of their academic profession. That by properly carrying out the actions of the administrative process and fulfilling the positions required to schedule the administrative activities of teachers, they contribute to compliance in a timely manner, achieving the commitment of the teacher who will support the exercise of his or her academic profession. Keywords: Administrative Management, University Teaching Commitment.